Assembling porous carbon-coated TiO2(B)/anatase nanosheets on reduced graphene oxide for high performance lithium-ion batteries. (10th November 2015) - Jiang, Shang; Wang, Runwei; Pang, Mingjun; Wang, Hongbin; Zeng, Shangjing; Yue, Xinzheng; Ni, Ling; Yu, Yanru; Dai, Jinyu; Qiu, Shilun; Zhang, Zongtao
Graphical abstract: Highlights: Porous carbon-coated mixed-phase Titanium dioxide nanosheets/reduced graphene oxide composites are successfully fabricated. Carbon coating has been achieved from organic components. Mesopores are uniformly distributed throughout the whole TiO2 @C nanosheet. Excellent cycling stability: the reversible capacity of 158.6 mAh g −1 is achieved at the current density of 800 mA g −1 after 500 cycles. Abstract: Novel porous carbon-coated mixed-phase porous TiO2 (TiO2 (B)/anatase) nanosheets/reduced graphene oxide composites (TiO2 @C/RGO) are successfully prepared through a facile one-pot solvothermal process followed by subsequent heat treatment in H2 /Ar. The as-formed composites have a hierarchical porous structure, involving an average pore size of 28.56 nm, a large pore volume of 0.589 cm 3  g −1 and a desired surface area (136.19 m 2  g −1 ). When used as an anode material in LIBs, TiO2 @C/RGO exhibits stable cycling performance with a reversible capacity of 272.9 mAh g −1 (with the second capacity retention of 151.1%) after 500 cycles at a current density of 100 mA g −1, much higher than that of TiO2 @C (177.6 mAh g −1, 123.9% of the discharge capacity in second cycle) and TiO2 (75.1 mAh g −1, corresponding to 96.5% of the original capacity). More impressively, the capacity of TiO2 @C/RGO can reach 158.6 mAh g −1 after 500 cycles even at 800 mA g −1 with Coulombic efficiency above 99.0%. The superior electrochemical performance of TiO2 @C/RGO may be attributed to its unique 3D hierarchical porous structures, the existence of carbon, large surface area and extremely reduced diffusion length.